2011
DOI: 10.1093/ntr/ntr145
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Radioactivity and Lung Cancer Risk

Abstract: The evidence of lung cancer risk caused by cigarette smoke radioactivity is compelling enough to warrant its removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…As the evidence for lethal impact of tobacco products started mounting, the companies created uncertainty and dispute regarding health risks, whilst at the same time had put lters on cigarettes and promised research into health effects of smoking to address growing public concern. Further, there are strong evidence from the Master Settlement Agreement in 1998 which shows that the radioactivity of tobacco smoke and its potential to cause cancer were known to TI, but they purposefully concealed this information [31]. In another instance in the USA, a network of consultants was developed by TI to advocate ventilation as a "remedy" to second-hand smoke (SHS) [32].…”
Section: Discussionmentioning
confidence: 99%
“…As the evidence for lethal impact of tobacco products started mounting, the companies created uncertainty and dispute regarding health risks, whilst at the same time had put lters on cigarettes and promised research into health effects of smoking to address growing public concern. Further, there are strong evidence from the Master Settlement Agreement in 1998 which shows that the radioactivity of tobacco smoke and its potential to cause cancer were known to TI, but they purposefully concealed this information [31]. In another instance in the USA, a network of consultants was developed by TI to advocate ventilation as a "remedy" to second-hand smoke (SHS) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Bretthauer e Black (1967) sugeriam a utilização de uma resina de troca iônica mista como um filtro para cigarros, na intenção de minimizar os efeitos do 210 Po para os tabagistas. A lavagem ácida foi descoberta em 1980 para ser altamente eficaz na remoção de 210 Po a partir das folhas do tabaco porém, assim como a alternativa anterior, não é aplicada porque a indústria tabagista considera prejudicial tal procedimento por ocasionar perda da chamada "nicotina kick", uma má absorção de nicotina no cérebro dos fumantes (KARAGUEUZIAN et al, 2011).…”
Section: Concentrações De 210unclassified
“…106,107 Cigarette butts and filters contain lead, arsenic and cadmium and an array of carcinogenic hydrocarbons. [12][13][14][15] More recent studies in Italian lead smelters have failed to substantiate a lung cancer risk for lead exposure, although the hazards of silicarelated pneumoconiosis and respiratory tract diseases were prevalent. 108 The mortality study of 1388 labourers employed in 1950-1992 showed that rates of lung, stomach and other cancers were actually lower than expected.…”
Section: Lung Tumoursmentioning
confidence: 99%
“…Stable and radioactive isotopes ( 210 Pb) of lead also occur in cigarettes and cigarette smoke and are carcinogenic in the lungs and respiratory tract in long-term smokers. [11][12][13][14] Induction of lung cancer is complex and may result from interactions among radioactive emissions, lead and numerous other carcinogens commonly present in cigarette smoke or related products. 15 …”
Section: Introductionmentioning
confidence: 99%